Assessment of freight traffic flows and harmful emissions in Euro-Mediterranean context: Scenario analyses based on a gravity model - Domenico Gattuso; Gian Carla Cassone; Domenica Savia Pellicanò (Journal of Shipping and Trade (JST), 2022)
Maritime transport contributes significantly to environmental pollution. The Mediterranean Sea Area is particularly affected by marine emissions from particulate matter, black carbon, nitrogen oxides and sulphur oxides. In addition to international and crossing traffic, the Mediterranean Sea is affected by the freight flows moved between its shores (in the North-South direction and vice versa), but also by transverse freight flows (East-West); these are freights transported through Short Sea Shipping. The Mediterranean Sea is the area where there is the highest concentration of short sea shipping in the EU-27. There are different types of Short Sea transport: container and bulk handling, general cargo ships and Ro-Ro transport. In such scenario, the analysis of trade flows as well as their spatial and geographical distribution, becomes fundamental. The paper proposes a gravity model for estimating trade flows, considering 18 countries boarding the Euro-Mediterranean Sea, in 2019. The proposed gravity model assumes that one of the main factors affecting trade is the economic dimension of a country which is directly related to the volume of imports and exports. In the paper, after a literature review on the gravity models, the illustration of the different phases investigation and construction of the database (specification, calibration and validation) to the definition and implementation of the proposed model is proposed. Scenario analyses are therefore proposed for assessing the environmental impacts generated by maritime transport in the Mediterranean basin as the freight flows vary. The analyses are carried out using a simulation approach which, starting from hypotheses on the economic and social development trends of the countries of the southern shore, made it possible to evaluate the variations in terms of freight flows and environmental impacts in terms of pollution.
Keywords: 650; Economic and social development; Environmental pollution; Gravity model; Maritime freight traffic; Mediterranean sea area; Simulation approach; Technologies; Trade flows